2021
DOI: 10.1080/03054985.2021.1973982
|View full text |Cite
|
Sign up to set email alerts
|

A capability approach to understanding academic and socio-emotional outcomes of students with special educational needs in Ireland

Abstract: How to cite:Please refer to published version for the most recent bibliographic citation information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…This finding was also true for teachers. A similar study indicated that parental expectations for young people with special education needs are much lower than those of the young people themselves (Mihut et al, 2022). Thus, parental expectations and engagement can have a significant effect on students' academic outcomes.…”
Section: Literature On Diversity and Students From Traditionally Excl...mentioning
confidence: 95%
“…This finding was also true for teachers. A similar study indicated that parental expectations for young people with special education needs are much lower than those of the young people themselves (Mihut et al, 2022). Thus, parental expectations and engagement can have a significant effect on students' academic outcomes.…”
Section: Literature On Diversity and Students From Traditionally Excl...mentioning
confidence: 95%
“…Concerns about segregated education, however, noted the overrepresentation of students from minority groups in special education provision and the stigma of labelling and civil rights issues. In other words, while arguments for the appropriateness of adapted, segregated, and specialised provision focused on the individual profile of the needs of pupils, actual practices within schools showed intersecting influences from wider societal and demographic factors [13,20,21]. Such concerns were also augmented by considerations regarding long-term impacts for pupils along their full life-span trajectories and how they could participate as citizens in society in the future.…”
Section: Educational Policy Movement Towards Inclusive Provisionmentioning
confidence: 99%
“…Concerns about segregated education, however, noted the overrepresentation of students from minority groups in special education provision and the stigma of labelling and civil rights issues. In other words, while arguments for the appropriateness of adapted, segregated, and specialised provision focused on the individual profile of needs of pupils, actual practices within schools showed intersecting influences from wider societal and demographic factors 13,20,21 . Such concerns were also augmented by considerations regarding long-term impacts for pupils along their full life-span trajectories and how they could participate as citizens in society in the future.…”
mentioning
confidence: 99%